Lithium excessively enhances event related beta oscillations in patients with bipolar disorder - Atagün, Murat İlhan; Güntekin, Bahar; Tan, Devran; Tülay, Emine Elif; BAŞAR, EROL (Elsevier Science Bv, Po Box 211, 1000 AE Amsterdam, Netherlands, 2015)
Background: Previous resting-state electroencephalography studies have consistently shown that lithium enhances delta and theta oscillations in default mode networks. Cognitive task based networks differ horn resting-state networks and this is the first study to investigate effects or lithium on evoked and event-related beta oscillatory responses of patients with bipolar disorder. Methods: The study included 16 euthymic patients with bipolar disorder on lithium monotherapy, 22 euthymic medication-free patients with bipolar disorder and 21 healthy participants. The maximum peak-to-peak amplitudes were measured for each subject's averaged beta responses (14-28 Hz) in the 0-300 ms time window. Auditory simple and oddball paradigm were presented to obtain evoked and event-related beta oscillatory responses. Results: There were significant differences in beta oscillatory responses between groups (p=0.010). Repeated measures ANOVA revealed location (p=0.007), laterality X group (p=0.043) and stimulus X location (p=0.013) type effects. Serum lithium levels were correlated with beta responses. Limitations: The lithium group had higher number of previous episodes, suggesting that patients of the lithium were more severe cases than patients of the medication-free group. Discussion: Lithium stimulates neuroplastic cascades and beta oscillations become prominent during neuroplastic changes. Excessively enhanced beta oscillatory responses in the lithium-treated patients may be indicative of excessive activation of the neuron groups of the certain cognitive networks and dysfunctional GABAergic modulation during cognitive activity. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Bipolar disorder; Brain oscillations; Event-related oscillations; Lithium; Euthymia; Induced Eeg Changes; Brain Oscillations; Euthymic Patients; Healthy-Subjects; Rating-Scale; Schizophrenia; Mechanisms; Matter; Synchronization; Abnormalities